ANALYSIS OF CREDIT RESTRUCTURING POLICY IMPLEMENTATION IN THE FRAMEWORK OF NATIONAL ECONOMIC RECOVERY DUE TO COVID-19 - Putri, Putu Ayu Diah Widari; Widyari, Nyoman Yudha Astriayu; Sari, Ida Ayu Komang Tiara Pratistha (LPPM Universitas Bina Bangsa, 2024)
The high credit risk during the Covid-19 pandemic requires effective solutions to maintain economic stability. To restore the economic and banking sectors, the government through the Financial Services Authority issued regulations to carry out credit restructuring. The aim of this research is to determine the implementation of credit restructuring policies and the criteria for debtors affected by Covid-19 who are entitled to credit restructuring at BPRs in Denpasar City. This research uses a case study research method. The results of this research show that the implementation of the restructuring policy due to Covid-19 provided by BPR in Denpasar City includes postponing interest payments, postponing principal payments and extending the term. Meanwhile, the criteria for debtors who are entitled to credit restructuring include all debtors who, according to the Bank's assessment of the submitted restructuring application, the debtor experiences problems in fulfilling their obligations because they are affected by the Covid-19 pandemic and the debtor has good business prospects to support credit quality and is able to fulfill their obligations after restructuring